A role for antibodies in natural HIV control. Issue 4 (July 2019) - Moris, Arnaud; Pereira, Mathias; Chakrabarti, Lisa
Abstract : Purpose of review: Rare patients naturally control HIV replication without antiretroviral therapy. Understanding the mechanisms implicated in natural HIV control will inform the development of immunotherapies against HIV. Elite controllers are known for developing efficient antiviral T-cell responses, but recent findings suggest that antibody responses also play a significant role in HIV control. We review the key studies that uncovered a potent memory B-cell response and highly functional anti-HIV antibodies in elite controllers, and explore the mechanisms that may account for the distinct properties of their humoral response. Recent findings: Elite controllers maintain a large HIV-specific memory B-cell pool that is sustained by efficient T follicular helper function. Neutralizing antibody rarely show high titers in controllers, but seem capable, at least in certain cases, of neutralizing contemporaneous viral strains. In addition, elite controllers display a unique HIV-specific antibody profile in terms of isotype, antigen specificity, and glycosylation pattern, resulting in polyfunctional antibody effector functions that may promote infected cell lysis and prime effectors of the antiviral immune response. Summary: Lessons from elite controller studies argue for the importance of integrating the many parameters defining a polyfunctional antibody response when evaluating candidate vaccines and immunotherapeutic approaches directed at HIV.